2015
DOI: 10.1021/cm503364s
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite Thin Films with Giant Electrical Polarization

Abstract: It is demonstrated that hydroxyapatite, a type of calcium phosphate commonly found in bone tissue, retains surprisingly large stored charge when synthesized electrochemically from aqueous solution. Thin films of hydroxyapatite formed on titanium and stainless steel electrodes were found to display giant polarization with quasi-permanent stored charge in excess of 70 000 microcoulombs per square centimeter. The polarization of the hydroxyapatite film develops during synthesis as a result of field-induced change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 43 publications
5
35
0
Order By: Relevance
“…The carbonate was probably caused by absorption of CO 2 from atmosphere during preparation under alkaline conditions [26]. Such carbonate composition was also observed in recently reported bone apatite that has 4-6% carbonate content [27]. For comparison, the HAP STR were also analyzed by FTIR.…”
Section: Hydroxyapatite Nanoparticles (Nhap) Synthesized By a High-grsupporting
confidence: 57%
“…The carbonate was probably caused by absorption of CO 2 from atmosphere during preparation under alkaline conditions [26]. Such carbonate composition was also observed in recently reported bone apatite that has 4-6% carbonate content [27]. For comparison, the HAP STR were also analyzed by FTIR.…”
Section: Hydroxyapatite Nanoparticles (Nhap) Synthesized By a High-grsupporting
confidence: 57%
“…Release of these molecules therefore must occur in part through diffusion through the composite film rather than only from the more rapid dissolution from the surface of the film. In addition, it is known that the surface of the HA layer formed in the first stage of the process is rich in negatively charge PO 4 3 − and OH − groups [32].…”
Section: Resultsmentioning
confidence: 99%
“…The local field strength in the Helmholtz layer can easily exceed 10 6 V/cm, and the high energy density of this layer is the basis for electrical storage in double layer capacitors [30,31]. Our group recently reported that the strong local fields result in an extremely large quantity of trapped ionic charge in electrochemically grown HA coatings [32]. In the present study, we modify the electrochemical synthesis of HA to trap non-reactive ionic species into the coating during synthesis.…”
Section: Introductionmentioning
confidence: 97%
“…9 These materials with improved d ij values exhibit square‐shaped hysteresis loops, termed as “ferroelectretic” 9. Recently, several approaches have been undertaken where the high electric poling field was avoided through careful synthesis of the in situ charged materials to serve as electrets, such as a silicon (Si) nanowires electret,10 zinc oxide (ZnO)/zinc sulfide (ZnS) core/shell electret,11 hydroxyapatite thin‐film electret12 etc. However, the preparation of such electret material requires multiple steps, and its inflexibility hindered the fabrication of suitable devices using these materials.…”
Section: Introductionmentioning
confidence: 99%